2022
DOI: 10.1002/emp2.12637
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Emergency Medicine Residency Programs’ use of social media in the setting of the COVID‐19 pandemic

Abstract: Objectives The coronavirus disease 2019 (COVID‐19) pandemic significantly affected the ability of residency programs and applicants to interact using traditional methods of in‐person interviews and visiting rotations. We examined the social media presence of emergency medicine (EM) residency training programs and how programs responded to the COVID‐19 pandemic. Methods The Electronic Residency Application Service (ERAS) identified EM residency programs that participated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Although Instagram was the most frequently used tool in our effort, Cox et al [ 19 ] have demonstrated significant expansion in general surgery programs’ Twitter use since the start of the pandemic. Similarly, emergency medicine residency programs increased social media use by 34% in 2020, and the authors felt the emphasis on web-based platforms in the setting of the pandemic was a significant catalyst [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although Instagram was the most frequently used tool in our effort, Cox et al [ 19 ] have demonstrated significant expansion in general surgery programs’ Twitter use since the start of the pandemic. Similarly, emergency medicine residency programs increased social media use by 34% in 2020, and the authors felt the emphasis on web-based platforms in the setting of the pandemic was a significant catalyst [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is worth noting the importance of programs’ online presence to potential EM applicants. As of 2021, nearly all EM residency programs in the United States have a website and a majority maintain at least one social media account 23 . Many of these accounts were created during the COVID‐19 pandemic in an effort to showcase programs to applicants who were unable to visit in person.…”
Section: How Do Applicants Select Potential Em Programs?mentioning
confidence: 99%